Українсько-російський словник-додаток до "Енеїди" І. Котляревського: біля витоків сучасної лексикографії - Козирєва, З. (Культура слова, 2019)
Статтю присвячено аналізу лексикографічного доробку зачинателя нової української літературної мови І.П. Котляревського. Зроблено спробу простежити вплив на наступні українські лексикографічні праці «Словаря Малороссійскихъ словъ содержащихся въ Енеидѣ и многихъ иныхъ въ Малороссии употребительныхъ, исправленный словами для четвертой части» І.П. Котляревського. Невеликий за розміром (1125 слів) і складений в основному до тексту одного твору додаток до «Енеїди» цінний і як перший українсько-російський словник з реєстром лексики нової української літературної мови, і як зразок для складання аналогічних словників при різних виданнях. Підкреслена роль Івана Котляревського як зачинателя і фундатора української авторської лексикографії у зв’язку зі створенням словника мови творчої особистості. The lexicographic activity of Ivan Kotlyarevsky, the founder of the new Ukrainian literary language, has constantly attracted and attracted the attention of researchers. The further in time his figure moves away from us, the more noticeable is his influence on the present. In the field of linguistic interests, the most prominent place is the issue of selection and extension of lexical and phraseological means, syntactic constructions of the author of “Aeneid”. Less attention is given to the research of I. Kotlyarevsky’s work as a lexicographer – the founder and sponsor of the author’s lexicography. The article attempts to trace the impact on the following Ukrainian lexicographic works of the Dictionary of the Lesser Russian words contained in “Aeneid” and many other Little Russians used for the fourth part of I. Kotlyarevsky. Small in size (1,125 words) and composed mainly to the text of the one work (“Aeneids”), Kotlyarevsky’s dictionary is valuable both as the first Ukrainian-Russian dictionary with a vocabulary register of the new Ukrainian literary language, and as a model for compilling similar dictionaries in different editions. The lexical and phraseological units, attested in the annex to the “Aeneid” in 1809, are traced to the presence in the following Ukrainian lexicographic works of the 19th – beginning of the 21st centuries. Particular emphasis is placed on the role of Ivan Kotlyarevsky as the originator of Ukrainian author’s lexicography in connection with the creation of the vocabulary of the creative personality language.